A New Evaluation on Four Golden Objects Recovered from the Necropolis of Parion - Keleş, V. (My University, 2014)
Being an important seaport on the Anatolian side of the Dardanelles Strait in the Propontis region, Parion is situated within the area of the town Kemer in the Biga district of the province Canakkale. Parion, propounded to be established in 709 BC according to the ancient resources, has always been an important seaport and military base in the military expeditions and commercial circulation between the Greek world and the Black Sea region. In Parion, Prof. Dr. C. Başaran and his team have undertaken surveys in the years 1997, 1999 and 2002 and they have been conducting scientific archaeological excavations since 2005.Four golden objects were recovered inside three stone cist graves in the southern necropolis of Parion in 2005. The previous publications stated that these golden materials were related to the "Kharon tradition". This has been reconsidered in this study and a new evaluation of these golden objects by considering the aspects of technicality, purpose of use and iconography have been suggested.
Parion Nekropolü'nde Ele Geçen Dört Altın Obje Üzerine Yeni Bir Değerlendirme
Keywords: Chest Stone Graves; Coins; Gold Wreath; Impression; Necropolis; Parion